2023
DOI: 10.1021/acs.cgd.2c01294
|View full text |Cite
|
Sign up to set email alerts
|

Triply-Reduced Hexa-peri-hexabenzocoronenes: Solid-State Structures and Magnetic Properties

Abstract: Discotic polycyclic aromatics have attracted great interest in both fundamental chemistry and material science due to their degenerate frontier orbitals, high molecular symmetry, unique solid-state packing, and ability to bear a certain number of unpaired electrons that can be applied in molecular spintronics and quantum computing. In this work, chemical reduction of hexa-perihexabenzocoronenes, HBC (1) and tBu-HBC (2), as "superbenzenes", has been investigated with K metal in THF solution. These reactions rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…21,37 These studies demonstrated their structural transformations, thus opening the way for investigations into the optical, electronic, and magnetic properties of the resulting solid crystalline materials. [38][39][40][41] Inspired by truxene's site-specic reactivity and interesting optical properties, we report the rst comprehensive study of the stepwise deprotonation of truxene with alkali metals (Na, K, and Cs). Products in different charging states have been isolated and fully characterized by single crystal X-ray diffraction, revealing the core curvature dependence on the charge and original metal complexation.…”
Section: Introductionmentioning
confidence: 99%
“…21,37 These studies demonstrated their structural transformations, thus opening the way for investigations into the optical, electronic, and magnetic properties of the resulting solid crystalline materials. [38][39][40][41] Inspired by truxene's site-specic reactivity and interesting optical properties, we report the rst comprehensive study of the stepwise deprotonation of truxene with alkali metals (Na, K, and Cs). Products in different charging states have been isolated and fully characterized by single crystal X-ray diffraction, revealing the core curvature dependence on the charge and original metal complexation.…”
Section: Introductionmentioning
confidence: 99%